2018
DOI: 10.1021/acs.jcim.8b00622
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Magnitude of σ-Holes Using VmaxPred, a Fast and Efficient Tool Supporting the Application of Halogen Bonds in Drug Discovery

Abstract: Halogen bonding as a modern molecular interaction has received increasing attention not only in materials sciences but also in biological systems and drug discovery. Thus, there is a growing demand for fast, efficient, and easily applicable tailor-made tools supporting the use of halogen bonds in molecular design and medicinal chemistry. The potential strength of a halogen bond is dependent on several properties of the σ-hole donor, e.g., a (hetero)­aryl halide, and the σ-hole acceptor, a nucleophile with n or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…The implementation of non-covalent interactions, such as hydrogen bonding, into supramolecular complex design in chemistry and biology is an attractive approach for molecular recognition. [1][2][3] Toward this pursuit, various avenues are being investigated to establish robust strategies that can encompass a wide variety of molecular design processes. Halogen bonding, a directional non-covalent interaction between a halogen atom (X) and a Lewis base (LB), [4][5][6][7] has been observed to facilitate strong and directional interactions in the solid state, solution, and gas phase and is well described with computational modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of non-covalent interactions, such as hydrogen bonding, into supramolecular complex design in chemistry and biology is an attractive approach for molecular recognition. [1][2][3] Toward this pursuit, various avenues are being investigated to establish robust strategies that can encompass a wide variety of molecular design processes. Halogen bonding, a directional non-covalent interaction between a halogen atom (X) and a Lewis base (LB), [4][5][6][7] has been observed to facilitate strong and directional interactions in the solid state, solution, and gas phase and is well described with computational modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The strong correlation of V max and the potential adduct formation energy (Politzer et al, 2013; Heidrich et al, 2018; Lange et al, 2019) and its demonstrated usefulness as descriptor for the magnitude of the σ-hole, is the basis for our choice of V max as an important parameter for our diversity assessment, which is centered on the XB interface. As an indicator for the diversity of our showcase HEFLib, we use the distribution of calculated V max values at the classical definition of the electron isodensity level of 0.001 au while including all possible tautomeric states with a net charge of zero.…”
Section: Resultsmentioning
confidence: 99%
“…Next evolutionary steps of the library are focused on three-dimensionality and even higher tuning values of V max . Since approximation of V max values can be efficiently performed using V max Pred (Heidrich et al, 2018), we plan to enrich fragments with greater σ-hole magnitudes by custom synthesis using carefully selected building blocks. Based on an in silico synthesis approach, vast numbers of potential halogenated fragments can be efficiently proposed and used as a starting point for a selection process as outlined herein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations